Melting Rate Determination of Mold Powders: Continuous Casting Process Versus Laboratory Conditions - Kölbl, Nathalie (Frontiers in Materials, 2022)
In the continuous casting of steel, the melting behavior of mold powders influences the slag pool thickness and slab quality. Various methods have been implemented in laboratories to investigate this property, and in particular, melting rates are of interest. This study aims to assess the existing methods with respect to their ability to determine melting rates under service-related conditions and to develop criteria for this purpose. These methods are divided into two groups, one of which can provide the necessary heat-transfer coefficient owing to the application of a preheated furnace or steel bath. The second condition is a sufficiently low mold powder layer thickness to allow for the desired mean heating rate. For the case study, the required heating rate is determined, and the maximum limit for this layer thickness is calculated from the conditions for Fourier and Biot numbers of varying test setups. Suitable test arrangements are also identified.